Biomass Derived N‐Doped Porous Carbon Supported Single Fe Atoms as Superior Electrocatalysts for Oxygen Reduction. Issue 22 (25th April 2017) - Zhang, Zhengping; Gao, Xinjin; Dou, Meiling; Ji, Jing; Wang, Feng
Abstract : Exploring sustainable and high‐performance electrocatalysts for the oxygen reduction reaction (ORR) is the crucial issue for the large‐scale application of fuel cell technology. A new strategy is demonstrated to utilize the biomass resource for the synthesis of N‐doped hierarchically porous carbon supported single‐atomic Fe (SA‐Fe/NHPC) electrocatalyst toward the ORR. Based on the confinement effect of porous carbon and high‐coordination natural iron source, SA‐Fe/NHPC, derived from the hemin‐adsorbed bio‐porphyra‐carbon by rapid heat‐treatment up to 800 °C, presents the atomic dispersion of Fe atoms in the N‐doped porous carbon. Compared with the molecular hemin and nanoparticle Fe samples, the as‐prepared SA‐Fe/NHPC exhibits a superior catalytic activity ( E 1/2 = 0.87 V and J k = 4.1 mA cm −2, at 0.88 V), remarkable catalytic stability (≈1 mV negative shift of E 1/2, after 3000 potential cycles), and outstanding methanol‐tolerance, even much better than the state‐of‐the‐art Pt/C catalyst. The sustainable and effective strategy for utilizing biomass to achieve high‐performance single‐atom catalysts can also provide an opportunity for other catalytic applications in the atomic scale. Abstract : Single Fe atom electrocatalyst, derived from biomass resource of porphyra as the biocarbon source and hemin as the natural iron source, presents atomic dispersion of Fe atoms in the N‐doped hierarchically porous carbon. The as‐prepared electrocatalyst exhibits much higher catalytic activity, durability, and methanol‐tolerance than the commercial Pt/C catalyst for oxygen reduction.